Critical role of cytochrome c1 and its cleavage in porcine reproductive and respiratory syndrome virus nonstructural protein 4-induced cell apoptosis via interaction with nsp4 - Feng ZHANG; Peng GAO; Xin-na GE; Lei ZHOU; Xin GUO; Han-chun YANG (Journal of Integrative Agriculture, 2017)
Porcine reproductive and respiratory syndrome virus (PRRSV) actively induces cell apoptosis both in vitro and in vivo, which can contribute critically to viral pathogenesis. Previous studies have shown that the PRRSV nonstructural protein 4 (nsp4) is an important mediator of this process, but the underlying molecular details remain poorly understood. In this study, we found that the PRRSV nsp4 interacted with the mitochondrial inner membrane protein cytochrome c1 (cyto.c1) and induced its proteolytic cleavage. Interestingly, the cleaved N-terminal fragment of cyto.c1 was found to exert apoptotic activity, which could cause mitochondrial fragmentation, resulting in apoptotic cell death. And RNA interference (RNAi) silencing experiments further confirmed the crucial role which cyto.c1 played in nsp4- and PRRSV-induced cell apoptosis. Thus, our data provide an important piece of mechanistic clues for PRRSV-induced cell apoptosis and also elucidate a novel mechanism for the 3C-like proteases in this finding.